Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Best Western The Lagoon Hotel Maadi - Punu Lesawengen, Gregor Reksi Ayub Punu (JURNAL ADMINISTRASI BISNIS, 2025)
This research was conducted to determine the effect of workload and work environment on employee performance of Best Western The Lagoon Hotel Manado. This research uses a quantitative approach and the population of Best Westen The Lagoon Hotel Manado employees is 47 employees. Data collection was carried out in several ways, namely interviews, questionnaires, field studies and literature studies, and the sample in this study used saturated sampling techniques, namely sampling of all existing employees, while the instrument used a Likert scale, with data processing using the SPSS version 30 application. The results in this study are partially (1) workload has no effect on employee performance, (2) work environment affects employee performance, (3) simultaneously workload and work environment affect employee performance.